Detection of low metal landmines using EMI - Azman, Amzarul Faris; Abdul Rahim, Ruzairi; Abdul Rahim, Herlina; Yunus, Yusri; Ahmad, Anita; Md. Yunus, Mohd Amri; Wahid, Herman (Penerbit UTHM, 2016)
Electromagnetic induction (EMI) sensors have been used extensively to locate buried landmines by detecting the metal present in such mines. Near field, EMI sensing from 10’s Hz up to 100’s of kHz has been successful in detecting metallic target. However, landmines vary in their construction from metal-cased varieties with a large mass of metal to plastic-cased varieties with minute amounts of metal. Unfortunately, there is often a significant amount of metallic debris (clutter) present in the environment. Consequently, EMI sensors that utilize traditional detection algorithms based solely on the metal content suffer from high false alarm rates. EMI sensors usually consist of a pair of coils, one of which is used to transmit either a broadband pulse or a continuous wideband electromagnetic waveform. The transmitted field induces a secondary current in the earth as well as in any buried conducting objects. In the case of pulsed excitation, the transmit waveform is quenched quickly and the receiving coil measures the decaying secondary field that has been induced in the earth and subsurface objects. In the case of wideband excitation, the receiving coil is placed within the magnetic cavity so that it senses only the weak secondary field radiated by the earth and buried objects. The phenomenology associated with EMI has been studied extensively. A simple phenomenological model that describes the measured time-domain waveform as a weighted sum of decaying exponentials has been shown to provide an accurate model for such sensors. In general, the decay rates associated with metallic objects are slower than that of the earth, so there is more energy in the received signal when a metallic object is present under the surface of the earth. This simple phenomenology allows very basic signal processing to be employed, for example either an energy detector or the overall amplitude of the signal in a given time gate, may be used when the goal is to detect any metallic subsurface object. However, in highly cluttered sites, such processing can be the source of many alarms.